(untitled) (PANGEEA, 2025)
The e-Learning well known benefits will be heightened when the learning procedure is personalized. Hence, e-learning should be dynamically personalized to both groups and individuals and in this case the same “digital” courses will be presented with different content variations to different virtual groups. As learners move through the content, the course content and the flow procedure will alter. For course designers, the idea of learning objects requires an immense change in thinking. Instead of looking at learning as a fixed linear progression with a restricted functionality, the research has to look at learning as clusters of independent, stand-alone objects of knowledge. These learning objects should be dynamically selected and sequenced by computer agents to form an individually tailored course. In this paper - supported by The Archimedes 2-2-17 Initiative - a set of XML schemas is introduced, that can be used as basic templates to wrap and tag reusable learning objects with enhanced GIS functionality.